A rotating fibrous-bed bioreactor for xanthan gum fermentation - Doma, Bonifacio T. (1999)
Xanthan gum is one of the most important polysaccharides. Its industrial production by fermentation is limited by oxygen transfer, which is due to the sudden increase in the apparent viscosity of the broth. An increase of 7.5% (w/v) in the xanthan concentration caused an approximately 1,210-fold increase in the apparent viscosity of the solution and a 52% drop in the solubility of the oxygen in the xanthan solution. The oxygen transfer is so severe that even at a lower product concentration (less than 3% w/v), the cells, Xanthomonas campestris, stop all of their biosynthetic activities. To remedy this problem, the pseudoplastic property of the xanthan gum solution was harnessed . By increasing the shear rate via the replacement of gravity with centrifugal force, the apparent viscosity of the xanthan solution can be decreased. To implement this effect, the original design of the rotating packed bed (RPB) was adopted, and from this, the new fibrous bed bioreactor (RFBB)system was developed. This RFBB system is an improvement of the centrifugal packed bed bioreactor (CPBB) by Lo et al. (1995). In this new system, a recirculating vessel was added in order for the bioreactor to be operated in a strictly gas-continuous mode and instead of bubbling sterile air in the fermentation broth, it was supplied directly at the bottom of the rotor through a sparger. The new bioreactor can be operated at a high rotational rate of 100 rpm, a radical improvement over the maximum rotational rate of 400 rpm of the CPBB.By recirculating the broth in the rotating packed bed, cells were retained ion the bed, allowing the fermentation to be operated in a series of repeated batches. The continuous reduction in the apparent viscosity of the broth, due to its constant recirculation in the rotating fibrous bed at a high pumping shear, allowed the fermemtation to proceed even at a relatively high xanthan concentration. The maximum product concentration obtained was ~75 g/L by far the highest reported value. The immobilization studies in X. campestris in 100% cotton fibers packed inside the rotating bed indicated that the mechanism is purely retentive and unstrict. The amount of cells retained was affected by the rotational and recirculation rates. Although fewer cells were immobilized at high rotational rates (about 20% at 800 rpm), these were enough to conduct the fermentation in a repeated batch mode without profound effects in the subsequent fermentation. The effects of the different operating parameters on the volumetric productivity and product yield were done during the repeated batches. It was found that the volumetric productivity increased with rotational rate and glucose-to-yeast extract ratio, but had no significant effect on the changes in the air flow rate. The highest volumetric productivity achieved was ~ 1.6 g L^-1 h^-1, a threefold increase relative to the conventional xanthan fermentation conducted in stirred tank bioreactors. Similarly, the xanthan fermentation in the RFBB has a characteristically high product yield, Yp/s. Fermentation done at rotational rates >=400 rpm has product yields greater than 88%. To have a better understanding of the characteristics of RFBB, studies on mass transfer, power consumption, average residence time, and liquid holdup were done against different design and operating parameters. In general, an increase in shear, caused by the increase in the applied centrifugal force or in the pumping rate, was translated into a mass transfer intensification. The volumetric mass transfer coefficient kLa', increased with increasing rotational and recirculation rates and with decreasing liquid volume. But it decreased with increasing xanthan gum concentration. In the purview of xanthan fermentation kLa' was found to have no significant dependency on iar flowrate due to the abwence of the bed pressure drop. Although the bed thcikness may have significant effect on kLa' the thickness of the bed used did not show any dependency.
For xanthan gum fermentation, the oxygen transfer rate (OTR) is more meaningful than kLa'. When the OTR was compared to the specific oxygen demand (SOD) of the X. campestris, the critical mass of the immobilized cells that can be supported by the system was found to decrease with increasing xanthan concentration. The power consumption of the RFBB was found to be affected solely by the rotational rate of the bed. Since the power consumption increased exponentially with the rotational rate, it can be correlated that mass transfer intensification is coupled with a concomitant increase in power consumption. With the use of a KCl tracer solution, the average residence times of the liquid elements inside the bed were found to be in the range of 9-42 s, depending on the liquid and gas rotational rates and the concentration of the xanthan solution. The average residence time of the liquid element was evaluated to be decreasing with increasing liquid or gas rotational rates and increasing with increasing xanthan gum concentration. THe liquid holdup inside the rotating bed was computed from the average residence time. A correlation was proposed for the liquid holdup vis-a-vis the ration of liquid and gas rates. Different mathematical models were adopted and modified to delineate the mass transfer specifics inside the RFBB during the pseudoplastic fermentation. It was found that rotating disk models (the complete convection-diffusion and penetration theory) are adequate to predict Kl, especially at high xanthan concentrations. Based on the rotating disk model and dimensional analysis, a correlation was derived by fitting the experimental data for the volumetric mass transfer coefficient for the proposed model. In turn, this correlation was used to predict the change of kL during the xanthan gum fermentation.
Thesis (Ph.D. Chemical Engineering)--University of the Philippines Diliman.
Keywords: Xanthan gum; Bioreactors; Fermentation